The environmental impact of cities - Newman, Peter (Sage Publications Ltd., 2006)
Cities are growing inexorably, causing many to think that inevitably their environmental impact will worsen. In this paper, three approaches to understanding the environmental impact of cities are analyzed, namely population impact, Ecological Footprint and sustainability assessment. Although the population impact model provides some perspective on local impact, and the Ecological Footprint model on global impact, only the sustainability assessment approach allows us to see the positive benefits of urban growth and provides policy options that can help cities reduce their local and global impact while improving their live-ability and opportunity, which continue to drive their growth. This approach is then applied in the city of Sydney.